A device for co-culturing autonomic neurons and cardiomyocytes using micro-fabrication techniques. Issue 3 (10th February 2016) - Oiwa, Kosuke; Shimba, Kenta; Numata, Takashi; Takeuchi, Akimasa; Kotani, Kiyoshi; Jimbo, Yasuhiko
Abstract : We developed a device for co-culturing sympathetic neurons, parasympathetic neurons, and cardiomyocytes using micro-fabrication techniques. Abstract : It is still unclear how the activity of sympathetic and parasympathetic neurons influences the activity of cardiomyocytes in culture. We developed a device for co-culturing sympathetic neurons, parasympathetic neurons, and cardiomyocytes using micro-fabrication techniques. Morphological connections between each type of autonomic neuron and the cardiomyocytes were observed by immunostaining. The inter-beat-interval (IBI) of the cardiomyocytes was modulated after electrically stimulating each type of autonomic neuron. Modulation of the IBI was blocked by the addition of pharmacological blockers to the culture medium. These results suggest that the co-culture device can be utilized to understand how the activity of sympathetic neurons and parasympathetic neurons influences the activity of cardiomyocytes in the culture environment.